2020
DOI: 10.1093/cercor/bhaa245
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Cerebral Processing of Abstract Linguistic Structure in Clear and Degraded Speech

Abstract: Human cortical activity measured with magnetoencephalography (MEG) has been shown to track the temporal regularity of linguistic information in connected speech. In the current study, we investigate the underlying neural sources of these responses and test the hypothesis that they can be directly modulated by changes in speech intelligibility. MEG responses were measured to natural and spectrally degraded (noise-vocoded) speech in 19 normal hearing participants. Results showed that cortical coherence to “abstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…Our statistical maps indicate that the experience-dependent enhancement of the tracking of phrase-and sentence-level responses are associated with activity in the left cerebral hemisphere. The lateralised responses are entirely consistent with the findings reported in our recent MEG study demonstrating that the speech intelligibility modulates changes in cortical tracking responses to larger linguistic units (phrases and sentences) (Meng et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our statistical maps indicate that the experience-dependent enhancement of the tracking of phrase-and sentence-level responses are associated with activity in the left cerebral hemisphere. The lateralised responses are entirely consistent with the findings reported in our recent MEG study demonstrating that the speech intelligibility modulates changes in cortical tracking responses to larger linguistic units (phrases and sentences) (Meng et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Our recent MEG study has demonstrated the effect of spectral degradation modulated speech intelligibility on these cortical tracking responses and investigated the underlying neural sources of the concurrent tracking responses (Meng, Li Hegner, Giblin, McMahon, & Johnson, 2021). Results of this study showed that cortical entrainment -the coherence between brain activities and "abstract" linguistic units with no accompanying acoustic cues (phrases and sentences) -was reduced parametrically as a function of reduced intelligibility.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations